Changes in Sleep Pattern and Digital Media use During Covid-19 Lockdown - Nadia Nisar, Qurat ul Ain Alam, M. Faisal Asghar, Roma Salman, Ambreen Javed, Hassan Burair Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out an association between covid and sleep and how covid lockdown has affected the sleeping habits of the youth in Pakistan compared to pre-lockdown sleeping patterns. Study Design: Cross-sectional study. Place and Duration: Current research was conducted at HITEC (IMS-HITEC) Institute of Medical Sciences, Taxila Cantt Pakistan from 5th may to 15th may 2020). Materials and Methods: It was a quantitative study in which participants filled out an online survey form. The data was collected on Google forms shared through social media focusing on undergraduate individuals from 16 to 24 years of age to acquire a homogenous example of responders, since youth are more liable to digital media use and their routine is more prone to be affected by the lockdown. The participation rate was 98.2%. SPSS was used for the data entry and analysis purpose. The data obtained was compiled, tabulated and analysed statistically. Chi square test was used to check whether the variables yielded significant or insignificant results. Results: Out of a total of 100 participants, 60 (60%) were females and 40 (40%) were males. The mean age was 21 years and the participants were mostly university students. A set of questions were also asked to determine which social media apps the participants were increasingly using, most of the participants spent time on Instagram (68%) and YouTube (64%), while modest people spent time on Netflix (41%), Snapchat (30%) and Facebook (33%). Lesser participants spent time on TikTok (11%) and Skype/Zoom (25%). Practical Implications: The use of e-learning and other forms of social interaction are becoming increasingly significant in the education of our young people. The findings of the current research make it possible for us to evaluate the influence of lockdown measures on Pakistani population in light of previously published studies that were carried out during the same time period in other countries and continents. Conclusion: Participants in the lockdown reported spending more time in front of screens and suffering delayed sleep habits. It was found that risky behaviours were associated with increased screen screen time.. Keywords: Sleep Pattern, Digital Media, Covid-19 lockdown, Screen Time, Social Applications